2017
DOI: 10.3389/fneur.2017.00312
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Dysfunction in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) commonly affects the cerebellum causing acute and chronic symptoms. Cerebellar signs contribute significantly to clinical disability, and symptoms such as tremor, ataxia, and dysarthria are particularly difficult to treat. Increasing knowledge concerning the pathophysiology of cerebellar disease in MS from human postmortem studies, experimental models, and clinical trials has raised the hope that cerebellar symptoms will be better treated in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 70 publications
2
75
2
3
Order By: Relevance
“…Further, structural and functional analyses have identified cerebellar abnormalities not only in primary cerebellar injury or degeneration, but also in many psychiatric and neurological diseases that degrade cognition and affect. Examples include major depressive disorder, anxiety disorders, bipolar disorder, schizophrenia, attention deficit and hyperactivity disorder, autism spectrum disorders 24 , posttraumatic stress disorder 25 , fibromyalgia 26 , Alzheimer's disease 27 , frontotemporal dementia 27 , vascular dementia 28 , Huntington's disease 29 , multiple sclerosis 30 and Parkinson's disease 31 . Unmasking the basic hierarchical principles of cerebellar macroscale organization can therefore have large impact in basic and clinical neuroscience.…”
Section: Introductionmentioning
confidence: 99%
“…Further, structural and functional analyses have identified cerebellar abnormalities not only in primary cerebellar injury or degeneration, but also in many psychiatric and neurological diseases that degrade cognition and affect. Examples include major depressive disorder, anxiety disorders, bipolar disorder, schizophrenia, attention deficit and hyperactivity disorder, autism spectrum disorders 24 , posttraumatic stress disorder 25 , fibromyalgia 26 , Alzheimer's disease 27 , frontotemporal dementia 27 , vascular dementia 28 , Huntington's disease 29 , multiple sclerosis 30 and Parkinson's disease 31 . Unmasking the basic hierarchical principles of cerebellar macroscale organization can therefore have large impact in basic and clinical neuroscience.…”
Section: Introductionmentioning
confidence: 99%
“…Tremors, which are either due to cerebellar or thalamic involvement, could occur, and they result in tremor affecting limbs, trunk, and vocal cord, and head. Types of tremors are intention, postural, rest, and rubral (Alistair [16]). Cerebellar signs will be evident with a significant involvement of the cerebellum.…”
Section: Cerebellummentioning
confidence: 99%
“…Similarly, the cerebellum has become clinically relevant for the study of not only primary cases of cerebellar injury or degeneration, but also neurology and psychiatry as a whole. Numerous studies have revealed that many neurological and psychiatric diseases that impair cognitive and affective processing include cerebellar functional and structural abnormalities (31)(32)(33)(34)(35)(36)(37)(38)(39). In this way, the present article describes the development of a novel, timely, and relevant neuroscience tool.…”
Section: Introductionmentioning
confidence: 96%